KNOWLEDGE AND USE OF CONTRACEPTIVES. FERTILITY FAMILY AND FITNESS FOR THE FEMALE POPULATION OF TRUJILLO - Guillén A., Félix (2015)
In order to determine the knowledge of contraceptive use, family use and fitness, has surveyed 400 patients alternately, in a representative sample of patients attending the General Teaching Hospital Base Health Center since November 1977 Trujillo until August of 1978. It is not possible to draw definitive conclusions from a survey; but it can be stated that we are facing a change of attitude in women who currently have more interest in controlling the number of children with spacing them. The sample accused predominance of married patients at 2.73 children per patient, low weekly income without desire to have more children. A high percentage ignores the use of contraceptives. Knowledge of contraceptives depends largely on the level of education, the income and marital status. The traditional rhythm method is the most used and known. Modern methods, the use of pills is the most widespread, but it is not well known use. The large family brings high percentage of economic, educational and health problems. The study population is not motivated to invest in education and health.